Phytoavailability and Leachability of Heavy Metals from Contaminated Soil Treated with Composted Livestock Manure. Issue 2 (17th February 2016) - Gul, Shazia; Naz, Alia; Khan, Abdullah; Nisa, Sobia; Irshad, Muhammad
ABSTRACT: A study was carried out with maize as the test crop to investigate the bioavailability and leachability of heavy metals (HM) from HM-contaminated soils treated with composted manure. The application of composted manure increased the maize shoot growth by 32.3% and root growth by 30.5% compared with fresh manure. The concentration of HM in maize shoot varied in the order lead (Pb) > nickel (Ni) > zinc (Zn) > chromium (Cr) > copper (Cu) > cadmium (Cd). Whether for the shoot or root, the heavy metal concentrations decreased as the length of manure composting increased, but concentrations were higher in the root than the shoot. Composting decreased the bioavailability and leachability of HM and, hence, their export to the environment more effectively than direct use of fresh manure. Thus, the use of composted manure in place of fresh manure in polluted soils would be more beneficial for mitigating HM pollution.